Chemical composition of Melina leaves (Gmelina arborea Roxb.) in three maturity stages - Vázquez Aguilar, Diego; Hernandez, Erika Andrea; Valadez Moctezuma, Ernestina; Hernández Sánchez, David (Ecosistemas y Recursos Agropecuarios, 2025)
Gmelina arborea Roxb. leaves are a food alternative in livestock production systems; however, the maturity state of the leaves and their nutritional quality are unknown. The objective of this study was to evaluate the chemical composition of G. arborea leaves at three maturity stages: young leaves (YL), adult leaves (AL), and mature leaves (ML), to determine their potential as forage. The content of Crude Protein (CP), Ether Extract (EE), and Ash (Ash), as well as Neutral Detergent Fiber (NDF), Acid Detergent Fiber (ADF), Lignin (Lig), Cellulose (Cel), and Hemicellulose (Hem), were evaluated using a completely randomized experimental design and mean comparison using Tukey's test (α = 0.05). AL had the highest CP content (P < 0.05) compared to YL and ML, which had values below 15%. AL had higher (P < 0.05) Ash content and lower EE (9.30% and 1.67%, respectively). NDF and ADF were higher (P < 0.05) in ML (42.09 and 31.38%, respectively) and lower (P < 0.05) in AL (34.66 and 24.99%, respectively). YL and ML showed higher (P < 0.05) Lig content (17 and 18%, respectively). There was no statistical difference in Cel and Hem between treatments. It is concluded that G. arborea leaves between 40 and 60 days old have adequate protein values, making them a good-quality forage for cattle.
Keywords: Forage trees; forage quality; nutritional composition